Two-Year Whey Protein Supplementation Did Not Enhance Muscle Mass and Physical Function in Well-Nourished Healthy Older Postmenopausal Women. Issue 11 (23rd September 2015) - Zhu, Kun; Kerr, Deborah A; Meng, Xingqiong; Devine, Amanda; Solah, Vicky; Binns, Colin W; Prince, Richard L
Abstract: Background: Protein may play a role in preventing muscle loss with aging. To our knowledge, there have been no long-term randomized controlled trials to examine the effects of increased dietary protein intake on muscle health in community-dwelling older women. Objective: In this study, we evaluated the effects of whey protein supplementation on muscle mass and physical function in community-dwelling older Australian women. Methods: In this 2 y randomized, double-blind, placebo-controlled trial, women aged 70–80 y (mean 74.3 ± 2.7 y) were randomly assigned to either a high protein drink containing 30 g of whey protein ( n = 109) or a placebo drink containing 2.1 g protein ( n = 110) daily. Dual-energy X-ray absorptiometry appendicular skeletal muscle mass, upper arm and calf (38% tibia) muscle cross-sectional area, physical function including hand grip strength, lower limb muscle strength and Timed Up and Go test, and 24 h urinary nitrogen were measured at baseline, 1 y, and 2 y. Results: A total of 196 women with at least one follow-up measurement were included in this analysis. Baseline mean BMI was 26.7 ± 3.9 kg/m 2 and protein intake was 76 ± 17 g/d (1.1 ± 0.3 g · kg body weight −1 · d −1 ). A mean increase in protein intake of ∼20 g/d in the protein group was confirmed by the estimates from 24 h urinary nitrogen. Over the 2 y in both groups there was a significant decrease in the upper arm (mean ± SE: −5.59 ± 0.75 cm 2 ) and calf (−0.77 ± 0.11 cm 2 ) muscle area, as well as hand grip strength (−1.30 ± 0.3 kg) (all P < 0.05), but appendicular skeletal muscle mass did not change significantly. There were no significant effects of the protein intervention on any of the muscle mass or physical function measures (all P > 0.05) at 1 and 2 y. Conclusion: This study showed that in protein-replete, healthy, ambulant, postmenopausal older women, 30 g/d of extra protein did not improve the maintenance of muscle mass or physical function despite evidence of deterioration in muscle measurements in the upper limb. This trial was registered at the Australian New Zealand Clinical Trials Registry as ACTRN012607000163404.